OPTIMALISASI SINTESIS KITOSAN DARI CANGKANG KEPITING SEBAGAI ADSORBEN LOGAM BERAT Pb (II) - Asni, Nurul; Saadilah, M. Arif; Saleh, Djonaedi (Jurnal Spektra, 2014)
Chitosan has been made from the crab shells with a chemical method with 1M HCl demineralization for 1 hour, deproteination 1M NaOH for 2 hours and variations of deacetylation 30% NaOH, 40%, 50%, 60%, and 70% for 45 minutes. An analytical methode from FTIR showed that the best chitosan deacetylation degree obtained at 50% NaOH, and the best reaction time to get the best Chitosan is 30 minutes.Chitosan product from crab shells is a real chitosan agreed with database Match! program. Chitosan is known best Pb adsorption from Pb(NO3)2 solution with concentrations of 10, 50, and 100 ppm acid dilution and neutral dilution of 25, 50, and 100 ppm for 30 minutes and tested variations chitosan residual liquid. Chitosan absorbed around 10 ppm Pb acid dilution and 25 ppm neutral dilution. No adsorption at 50 and 100 ppmPb in acid dilution. Absorption of 44.77 ppm at 50 ppm and 97.04 ppm to 100 ppm.Keywords: Chitosan,Adsorption, Pb